Immunometabolism of Macrophages in Bacterial Infections - Galli, Gaël; Saleh, Maya (Frontiers in Cellular and Infection Microbiology, 2021)
Macrophages are important effectors of tissue homeostasis, inflammation and host defense. They are equipped with an arsenal of pattern recognition receptors (PRRs) necessary to sense microbial- or danger-associated molecular patterns (MAMPs/DAMPs) and elicit rapid energetically costly innate immunity responses to protect the organism. The interaction between cellular metabolism and macrophage innate immunity is however not limited to answering the cell’s energy demands. Mounting evidence now indicates that in response to bacterial sensing, macrophages undergo metabolic adaptations that contribute to the induction of innate immunity signaling and/or macrophage polarization. In particular, intermediates of the glycolysis pathway, the TCA cycle, mitochondrial respiration, amino acid and lipid metabolism directly interact with and modulate macrophage effectors at the epigenetic, transcriptional and post-translational levels. Interstingly, bacterial pathogens usurp macrophage metabolic pathways to attenuate anti-bacterial defenses. In this review, we highlight recent evidence describing such host-bacterial immunometabolic interactions.